Prevalence and consultation behavior of self-reported rectal bleeding by face-to-face interview in an Asian community - Basaranoglu, Metin; Celebi, Selman; Ataseven, Huseyin; Rahman, Suheyla; Deveci, S. Erhan; Acik, Yasemin (Karger, 2008)
Background and Aim: Although rectal bleeding is a common gastrointestinal symptom, there are very few community-based studies, and all of these studies were conducted in the West. So far the epidemiologic characteristics of rectal bleeding have not been defined in an Asian country. We aimed to characterize self-reported rectal bleeding and its association with functional bowel disorders in Turkey. Factors affecting healthcare-seeking behavior were reviewed as well. Subjects and Methods: In this study, 760 subjects were chosen randomly. Questionnaires were completed by nurses during face-to-face interviews with each participant. Results: Of the 707 (93%) subjects included in this study, 9.5% had functional dyspepsia, 8.6% had irritable bowel syndrome (IBS), 24.5% had functional constipation, and 13.8% had functional abdominal bloating. The prevalence of rectal bleeding in the previous year was 14.7%. The recent onset of rectal bleeding was 2.7%. Rectal bleeding was more common among subjects younger than 45 years. Subjects who had functional constipation or constipation-dominant IBS reported rectal bleeding more frequently than others. The rate of consultation was only 41.3% among the subjects with rectal bleeding. Subjects aged >= 45 years and who had marked bleeding or bleeding more than twice a day or fear of cancer sought healthcare more frequently than others. Conclusion: Rectal bleeding is as common a symptom in Turkey as in Western countries. Advanced age and fear of cancer were independent predictors of consultation behavior in this group.
Keywords: rectal bleeding; prevalence; consultation behavior; functional bowel disorders